2021
DOI: 10.6061/clinics/2021/e2741
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Postoperative Infection in Cancer Patients Undergoing Spine Surgery

Abstract: To determine the rate of and main risk factors for postoperative infection in cancer patients who underwent spine surgery in the last 5 years in order to determine whether there is an association between postoperative infection and increased mortality during hospitalization. METHODS: All cancer patients who underwent surgical procedures between January 2015 and December 2019 at a single hospital specializing in spine cancer surgery were analyzed. The primary outcome of interest was postoperative infection. Biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…While past research has explored the incidence and risk factors of wound complications in spinal metastasis tumor surgery, the majority of these studies were limited by being conducted at single institutions with fewer patients [2,4,6,15,22]. As a result, their findings were often heterogenous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While past research has explored the incidence and risk factors of wound complications in spinal metastasis tumor surgery, the majority of these studies were limited by being conducted at single institutions with fewer patients [2,4,6,15,22]. As a result, their findings were often heterogenous.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that various surgical-related factors contribute to an increased risk of wound complications, and particularly, the risk increases as the extent of the surgery becomes more extensive [2,6,7]. While there are cases where more extensive surgery is necessary, accepting the risk of wound complications such as paralysis, there is also deliberation in cases of asymptomatic nerve compression as to whether to make the surgery more extensive by adding decompression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A surgical site infection (SSI) is one of the most common complications occurring after spinal surgery, with incidence rates ranging from 0.7% to 12% 1–3 . Despite the implementation of systematic prevention strategies in clinical practice, SSIs remain a concern for surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…A surgical site infection (SSI) is one of the most common complications occurring after spinal surgery, with incidence rates ranging from 0.7% to 12%. [1][2][3] Despite the implementation of systematic prevention strategies in clinical practice, SSIs remain a concern for surgeons. Many risk factors are associated with spinal SSIs, including diabetes, hypertension, smoking, alcohol abuse and steroid use.…”
Section: Introductionmentioning
confidence: 99%